Movilidad peatonal sostenible en el espacio público de la zona céntrica de El Cerrito Valle del Cauca - Bejarano Parra, Daniel Alejandro (Universidad Antonio Nariño, 2021)
The present research work, consists of the development of urban intervention guidelines on public spaces from downtown of El Cerrito Valle del Cauca, starting to improve the quality of life, satisfying basic needs of the inhabitants that are mobilized in a pedestrian way; These guidelines will be developed for the improvement of urban condition of inhabitants from downtown and inhabitants of the municipally in general, based on a qualitative and quantitative study, considering the historical evolution in terms of mobility that has had the municipality through its 194 years since was founded, implementing sustainability, as an important subject for the development. This zone counts with problems such as inadequate use, lack of pedestrian paths, lack of parking lots, architectonics elements that have turned into barriers through the development of the municipality, the few public spaces that exist for pedestrian mobility, and lack of urban furniture. That analysis will help us to raise strategies for the development of quality of life for their inhabitants.